Faktor Risiko Kejadian Tb Paru di Wilayah Kerja Puskesmas Rawat Inap Sidomulyo - Emi Yulita; Carles Carles; Awaluddin Awaluddin; Erika Erika (Universitas Pahlawan Tuanku Tambusai, 2025)
Tuberculosis is an infectious disease caused by the bacillus Mycobacterium tuberculosis. Until now, tuberculosis remains a major health problem, both globally and in Indonesia, where it has become a global concern for the past 2 decades. The purpose of this study was to determine the risk factors for pulmonary TB in the working area of the Sidomulyo Inpatient Health Center. This study was an observational analytic with a case control study design. This study was conducted in March 2023 - March 2024 at the Sidomulyo Inpatient Health Center. The results of the bivariate study from 10 variables showed that 6 variables had no relationship with the incidence of pulmonary TB, including; nutritional status with a p value of 0.429, residential density with a p value of 0.580, temperature with a p value of 0.0783, humidity with a p value of 0.0783, ventilation with a p value of 0.582 and floor type with a p value of 0.169. Based on these results, the dominant variables were analyzed using multiple logistic regression multivariate analysis where age had an influence on the incidence of pulmonary TB of 0.005 <0.05, gender obtained a p value of 0.005 <0.005, as well as knowledge obtained a p value of 0.041 <0.005 and smoking status obtained a p value of 0.000 <0.005. Furthermore, based on the output, the R-square value is 0.474. This indicates that the determining variable simultaneously affects pulmonary TB by 47.4%. Recommendation: It is necessary to broaden your knowledge by seeking various information on tuberculosis control efforts in the residential environment and its surroundings